1994
DOI: 10.1002/prep.19940190402
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and prediction of the heats of formation for non‐aromatic polynitro compounds on the basis of the QSPR approach

Abstract: The analysis of “Quantitative Structure‐Property Relationship”(QSPR), concerning the heat of formation in the condensed state, is performed for non‐aromatic polynitrocompounds. The QSPR approach and our original computer program “EMMA”(Efficient Modelling of Molecular Activity) are used. This approach is based on the construction of optimal linear regression models involving physical‐chemical, topological, informational, and substructural indices; it can be used as an alternative to traditional additive scheme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Effective modeling of molecular activity statistical program has been used to develop models . It allows obtaining different regression models with different combinations of parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective modeling of molecular activity statistical program has been used to develop models . It allows obtaining different regression models with different combinations of parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, mostly in adults, showed that neutrophil VCS parameters were useful in the diagnosis of sepsis [6,10,11,17,18]. Effective modeling of molecular activity statistical program has been used to develop models [19,20,21]. It allows obtaining different regression models with different combinations of parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The earlier versions [1,2] of LOTUSES code (version 1.1 and 1.2) also require heat of formation as an input parameter. Therefore, it can be realised that heat of formation is a vital parameter for the performance prediction of explosives and propellants [9][10][11]. The interdependence of these parameters in the field of HEMs is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Errors were usually less than ± 5 to 10 kcal/mole which may be considered as very encouraging, given the fact that the procedure uses only molecular structural information. Table 1 [17][18][19][20] shows comparative data of experimental and predicted heat of formation of three classes of molecules of aliphatic, aromatic, and ring structures, containing nitro and other energetic groups [17][18][19][20] . Errors for molecules containing -O-NO 2 were found to be on a higher side.…”
Section: Resultsmentioning
confidence: 99%